The Bacterial and Viral Complexity of Post-infectious Hydrocephalus in Uganda - Paulson, Joseph N.; Williams, Brent L.; Hehnly, Christine; Mishra, Nischay; Sinnar, Shamim A.; Zhang, Lijun; Ssentongo, Paddy; Kabachelor, Edith Mbabazi; Wijetunge, Dona S. S.; Bredow, Benjamin von; Mulondo, Ronnie; Kiwanuka, Julius; et al. (Science translational medicine, 2020)
Postinfectious hydrocephalus (PIH), often following neonatal sepsis, is the most common cause of pediatric hydrocephalus world-wide, yet the microbial pathogens remain uncharacterized. Characterization of the microbial agents causing PIH would lead to an emphasis shift from surgical palliation of cerebrospinal fluid (CSF) accumulation to prevention. We examined blood and CSF from 100 consecutive cases of PIH and control cases of nonpostinfectious hydrocephalus (NPIH) in infants in Uganda. Genomic testing was undertaken for bacterial, fungal, and parasitic DNA, DNA and RNA sequencing for viral identification, and extensive bacterial culture recovery. We uncovered a major contribution to PIH from Paenibacillus, upon a background of frequent cytomegalovirus (CMV) infection. CMV was only found in CSF in PIH cases. A facultatively anaerobic isolate was recovered. Assembly of the genome revealed a strain of P. thiaminolyticus. In mice, this isolate designated strain Mbale, was lethal in contrast with the benign reference strain. These findings point to the value of an unbiased pan-microbial approach to characterize PIH in settings where the organisms remain unknown, and enables a pathway towards more optimal treatment and prevention of the proximate neonatal infections.
Keywords: Hydrocephalus; Neurosurgery in children; Microbial agents